Coil Offset Based Wireless Power Transfer System Parameter Optimization - Xiaojuan CHEN; Min JIA; Mingchen LI (Zhongguo dianli)
In a magnetic coupling resonant wireless power transmission system, the relative position of the system coil is one of the main factors affecting its transmission performance. This article focuses on the efficiency loss caused by the offset of the coil in the traditional power transmission system, and proposes a Firefly algorithm based parameter design method to optimize the efficiency of the coil when placed non-coaxially. Firstly, the analysis of the mutual inductance of the coil at different positions is carried out, and then the bilateral LCC topology is applied to examine its transmission performance. The parameters optimization is carried out using the firefly algorithm, and finally the effectiveness of the method is verified through a finite element simulation and experimental platform. The results show that when the offset distance is less than the radius of the coil, the transmission efficiency of the system can maintain more than 85%, which is similar to the traditional SS topology of WPT. In comparison, the transmission efficiency of the optimized system is increased by an average of 20%, and the received power of the load remains at about 20 W.